(untitled) (Journal of Applied Learning and Teaching, 2019)
This is the third book that I have reviewed in the series, Perspectives on Leadership in Higher Education, published by Bloomsbury. The book is written within the context of leadership involving interconnectivity with staff and building consensus on future strategies to embrace the issues confronting universities. The book is written around the challenges facing universities in an increasingly corporatised environment facing challenges of marketisation, internationalisation and the need to agree on approaches to deal with increasing global complexity and fragmentation. It is interesting to reflect on styles of leadership across society in the current era. At the highest political levels, we are finding it increasingly difficult to build a majority consensus on approaches to things like climate change, migration and economic policy settings. Politics in democratic societies have become dominated by populist politicians and coalitions of minority groups pushing for individual agendas rather than a collective agenda as may have been apparent in the past. In other parts of the world, authoritarian rule has been strengthened.